Growth and mortality of bronze croaker,Otolithoides biauritus (Cantor) fromMumbai waters - Chakraborty, Sushanta Kumar (Indian Journal of Fisheries, 2011)
Investigation on the growth and mortality of Otolithoides biauritus (Cantor)based on the length frequency data from April 1994 to May 1997 is reported inthe present communication.Â The asymptotic length (Lâˆž) was calculated as178.2 cm and growth coefficient (K) as 0.58 yr-1 .Â The total mortality coefficient(Z) was estimated as 2.02 wherein the natural mortality coefficient (M) was0.734 and the fishing mortality coefficient (F) was 1.286. The Z/K of 3.48 of thisspecies indicate high levels of exploitation.Â However, O. biauritus has with-stood the high fishing pressure of the shrimp trawlersÂ with a faster growthrate, high fecundity and offshore breeding.Â In recent years, though there hasbeen a revival in the fishery in terms of total catch, the quantum of juvenileslanded is still very high, which is detrimental for the stock.